THE USE OF ZOOSEMISM IN UZBEK AND ENGLISH LITERATURE - Ergasheva Sevara O’tkir qizi Samarqand davlat chet tillari universiteti magistranti Ilmiy rahbar: PhD. dotsent Rustamova Adash Eshankulovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article explores the phenomenon of zoosemism, the literary device that attributes animal qualities to humans or human behaviors, in both Uzbek and English literature. The author delves into the historical and cultural contexts of Uzbek and English literary traditions to examine how zoosemism has been utilized as a means of conveying deeper symbolic and allegorical meanings